2006 IEEE International Reliability Physics Symposium Proceedings 2006
DOI: 10.1109/relphy.2006.251259
|View full text |Cite
|
Sign up to set email alerts
|

NBTI: An Atomic-Scale Defect Perspective

Abstract: We utilize a combination of MOSFET-gate controlled diode DC-IV measurements and a very sensitive electrically-detected electron spin resonance technique called spindependent recombination to observe and identify defect centers generated during NBTI in fully processed SiO 2 and plasma nitrided oxide (PNO)-based pMOSFETs. In SiO 2 devices, we observe the NBTI-induced generation of two Si/SiO 2 interface silicon dangling bond centers (P b0 and P b1 ) and very likely an oxide silicon dangling bond center (E′). Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…In addition to time exponents, the activation energy of NBTI is also extensively studied in pre-2003 literature and various report suggest that E A $ 0.12-0.15 eV [1,8,20,28]. If we assume that…”
Section: The R-d Model Of Nbti Degradation: Definition Of the Puzzlementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to time exponents, the activation energy of NBTI is also extensively studied in pre-2003 literature and various report suggest that E A $ 0.12-0.15 eV [1,8,20,28]. If we assume that…”
Section: The R-d Model Of Nbti Degradation: Definition Of the Puzzlementioning
confidence: 99%
“…Since the specific values of activation energies of forward dissociation, E F , reverse annealing, E R , and diffusion coefficient, E D , were unknown, the inconsistency between time-exponent n and temperature activation E A was initially not highlighted. However, generalized scaling arguments consistently showed that E A $ E D /n [1,4], with E F $ E R [1,2,4,28]. The measured E A therefore provided a direct measure of E D $ 0.5-0.6 eV, which in turn implicated H 2 diffusion [29]!…”
Section: The R-d Model Of Nbti Degradation: Definition Of the Puzzlementioning
confidence: 99%
“…To reach this aim a new embedded-power 120nm technology has been developed offering high performance LDMOS devices for 12V and 24V with a thin 5.2nm gate oxide, a novelty for these voltage classes. We achieved a new industry benchmark of R ON equal to 4mΩ×mm 2 @BVdss=20V, but several challenges had to be solved for a productive reliable technology [1][2][3][4][5][6][7][8][9][10][11][12][13]. The transistors have to be optimized to achieve reliable Safe Operating Area (SOA) with low device R ON (high efficiency) and targeted breakdown voltages.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most vexing problems of conventional Si/SiO 2 and SiO 2 /nitrided oxide MOS devices is the negative bias temperature instability (NBTI) which causes reduced drain current and shifts in threshold voltage when pMOSFETs are subjected to a negative gate bias, typically at an elevated temperature [1][2][3][4] . Although progress has been made recently in identifying atomic scale NBTI induced defects in Si/SiO 2 based devices [5][6][7] , not much is known about NBTI defects in high-K based MOS devices. In this study, we combine electrical and magnetic resonance measurements to investigate the atomic scale mechanisms of NBTI in HfO 2 based devices.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 compares moderately short term and long term NBTI SDR traces from a representative Si/SiO 2 device 7 . The poly gate SiO 2 devices has an equivalent oxide thickness of 75 nanometers [5][6][7] . A precise match between SDR measurements of NBTI defects in HfO 2 and SiO 2 based devices isn't possible because, in the SiO 2 based devices, strong recovery effects preclude SDR observations for very short times at any temperature.…”
Section: Introductionmentioning
confidence: 99%